Variation of Peat Bulk Density and Carbon Density under Several Land Use Types - I G.P. Wigena; Setiari Marwanto; Jubaedah Jubaedah (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2013)
Abstract. Assessment of peat carbon stock is very important in the estimate of long term carbon stock changes and hence carbon emissions from peat soil. We studied lateral and vertical variation of Bulk density (BD), carbon (C) content, and C density of primary forest and drained peatland under several drained land use types, namely Acacia mangium, bare land, oil palm, rubber, and secondary forest. The study was done at Lubuk Ogong Village, Sei Kijang Districts, Pelalawan Regency, Riau Province from 2011 to 2012. Peat samples were taken at the distances of 15, 30, 45, 60, and 75 meter on transect perpendicular to the drainage canal on each selected land use. Another site was Sri Menanti Village, Betara District, West Tanjung Jabung Regency, Jambi Province, on two land use types, namely oil palm and rubber plantations and primary peat forest of Berbak National Park. Soil samples were taken at the distances of 10, 25, 50, and 100 m perpendicular to the drainage canal. The vertical variations of C-content showed a common pattern, around 54.29 ± 1.60% in upper (0-200 cm) layer, around 56.70 ± 0.37% in middle (200-400 cm) layer, and around 37.88 ± 16.33% in the lower (>400 cm) layer. In contrast, BD and C-density were high in upper layer of around 0.17 ± 0.03 and 88.26 ± 16.61 kg m-3; 0.11 ± 0.02 and 56.86 ± 16.61 kg m-3 in the middle layer and increased to 0.24 ± 0.10 g cm-3 and 86.59 ± 14.02 kg m-3 in the lower layer, respectively. The soil C-content under oil palm plantation was around 49.31 ± 0.89% in the upper, 52.63 ± 2.72% in the middle, and 44.55 ± 8.25% in the lower layer. However, rubber and primary forest showed a different pattern, with a high C content of 52.47 ± 0.85% in upper layer, 45.10 ± 7.67% in the middle and 35.72 ± 1.74% in the lower layer. The vertical variations of C-density was 68.8 ± 12.5 kg m-3 in the upper, 53.3 ± 25.2 kg m-3 in the middle, and 72.34 ± 19.4 kg m-3 in the lower layer. Under rubber plantation the C density decreased with depth where the upper layer contained 55.09 ± 5.73 kg m-3, the middle layer 48.71 ± 7.61 kg m-3 and the lower layer 41.19 ± 6.82 kg m-3. This variation and unclear pattern requires the whole profile measurement of C content and BD for the assessment of peat C stock.